Advertising and engagement in Tik Tok: Analysis of the strategies used by Nude Project and Pull & Bear to connect with generation Z - González Oñate, Cristina; Briz Casado, Karla (Documentación de las Ciencias de la Información, 2026)
The advent of social networks has completely transformed the way companies communicate with their audiences. In this context, Tik Tok has broken through in terms of its viralization model and its connection with young people. In a social environment characterized by instant consumption, hyper-personalization and content saturation, brands today face the challenge of capturing the difficult attention of a new generation, Generation Z, which prioritizes authenticity, emotional connection and entertainment over the traditional advertising of conventional media. This paper analyzes how two fashion brands, Nude Project and Pull and Bear, adapt their advertising strategies to the particularities of this platform. It is based on the hipothesis that it is not the investment in video promotion that generates the greatest impact, but the ability of a brand to integrate organically into the dynamics of the Tik Tok algorithm and connect emotionally with users. The methodology is carried out though a qualitative and quantitative analysis of the content and its main metrics of the videos published by the official Tik Tok accounts of Pull and Bear and Nude Project between October 2024 and January 2025 and is complemented by a survey directed to users of the platform. The results reflect which types of videos get higher engagement rates and why. Thus, this research offers a current view of the impact of Tik Tok in the advertising strategy of brands and highlights the importance of authenticity as a key to connect with the new generations.